Mengungkap Peran Norma Subjektif, Cinta Merek, dan Advokasi Merek terhadap Niat Beli: Studi pada Pembelian Online Saat Even Harbolnas - Hartoyo, Yulia Nuraeny; Sutarso, Yudi (Universitas muhammadiyah palembang, 2024)
National Online Shopping Day has become a phenomenon that attracts public interest in shopping through online platforms. National Online Shopping Day is an annual event that involves ownership and highlighting through online platforms that are often held in certain countries or regions, so that a number of e-commerce sites and online stores provide massive discounts, targeted promotions, and other special offers to customers. This study aimed to analyze the mediating role of price sensitivity in linking factors such as subjective norms, behavior, brand love, brand advocacy, and purchase intent during National Online Shopping Day. This study used quantitative research with descriptive analysis techniques using WARP-PLS. The sampling technique used is non-probability sampling with purposive sampling techniques. The sample of this study was 149 users of National Online Shopping Day in Surabaya and Sidoarjo. The results of this study showed that subjective norms had no effect on attitudes. In addition, subjective norms influence purchase intent, brand love, and brand advocacy. The role of attitude also influences purchase intent and brand love. Brand love influences purchase intent and brand advocacy, as does the role brand advocacy plays in influencing purchase intent. The role of price sensitivity is also quite large but is not able to moderate the relationship between subjective norms to attitudes